Predictors of Incisional Hernia after Robotic Assisted Radical Prostatectomy - Avinash Chennamsetty; Jason Hafron; Luke Edwards; Scott Pew; Behdod Poushanchi; Jay Hollander; Kim A. Killinger; Mary P. Coffey; Kenneth M. Peters (Advances in Urology)
Introduction. To explore the long term incidence and predictors of incisional hernia in patients that had RARP. Methods. All patients who underwent RARP between 2003 and 2012 were mailed a survey reviewing hernia type, location, and repair. Results. Of 577 patients, 48 (8.3%) had a hernia at an incisional site (35 men had umbilical), diagnosed at (median) 1.2 years after RARP (mean follow-up of 5.05 years). No statistically significant differences were found in preoperative diabetes, smoking, pathological stage, age, intraoperative/postoperative complications, operative time, blood loss, BMI, and drain type between patients with and without incisional hernias. Incisional hernia patients had larger median prostate weight (45 versus 38 grams; P=0.001) and a higher proportion had prior laparoscopic cholecystectomy (12.5% (6/48) versus 4.6% (22/480); P=0.033). Overall, 4% (23/577) of patients underwent surgical repair of 24 incisional hernias, 22 umbilical and 2 other port site hernias. Conclusion. Incisional hernia is a known complication of RARP and may be associated with a larger prostate weight and history of prior laparoscopic cholecystectomy. There is concern about the underreporting of incisional hernia after RARP, as it is a complication often requiring surgical revision and is of significance for patient counseling before surgery.